ANALISA KAPASITAS TINGKAT PELAYANAN LALU LINTAS PADA PEREMPATAN JALAN RAYA LANGSEP KELURAHAN TANJUNGREJO KOTA MALANG - Arnoldus Moruk, Dionisius; Pandulu, Galih Damar; Rahma, Pamela Dinar (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Malang is the second major city after the city of Surabaya in East Java with tourist potential and its economy is growing. The activities such as malls, markets, parks, campuses, tourist areas, office activities and other activities are factors that make this street has a solid activity that resulted in the problem - the problem of transport one road congestion resulting in decreased capacity, In a survey or research used data collection methods with Manual Method Counter at the intersection of Highway langsep Village Tanjungrejo Malang for the purpose of calculating the value of traffic volume, capacity and level of service is to conduct a survey for 7 days and two weeks starting at 6:00 pm - 22:00 pm) and the results of the survey obtained data on the volume of traffic, road geometric data were then analyzed using the Indonesian highway Capacity Manual (MKJI) 1997. Based on the analysis, the volume of peak hour at the intersection of highways langsep is 3554.9 smp / hour , capacity of 2889.56 smp / hour and the level of service (LOS) is F. Keywords: Analysis, capacity, degree of saturation and analysis service levels.